Silicon-boron-phosphorus alloy negative electrode material and preparation method and application thereof
By embedding porous carbon in the silicon negative electrode material and doping phosphorus and boron to form a silicon boron-phosphorus alloy negative electrode material, the problem of insufficient processing performance and structural strength of existing silicon negative electrode materials is solved, and electrochemical performance with high capacity, high magnification and ultra-long cycle is achieved.
Patent Information
- Application Number
- CN202411793721.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-25
AI Technical Summary
The existing silicon negative electrode materials have shortcomings in terms of processing performance and structural strength, which has caused the cycle performance to be affected and it is difficult to meet market demand.
Through a preparation method, biomass raw materials are used to pre-carbonize to form porous carbon materials, and vapor-phase deposition of silicon, boron and phosphorus is carried out in the protective atmosphere to form a silicon boron and phosphorus alloy negative electrode material. Silicon deposition is embedded in porous carbon, and phosphorus is doped in the nanosilicon particles in the core, and body phase defects are introduced by boron elements to maintain the stability of the material structure.
The prepared silicon borophosphorus alloy negative electrode material has the characteristics of high capacity, high magnification and ultra-long cycles, excellent electrochemical stability, the capacity of lithium-ion batteries reaches 1650-2250mAh/g, the first efficiency is 89-93%, and the capacity retention rate is 92.1% after 50 weeks of circulation.
Smart Images

Figure CN119695130A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a silicon-boron-phosphorus alloy negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion secondary batteries are widely used in portable electronic products, electric vehicles, and energy storage due to their high mass and volume energy density, long cycle, and low self-discharge performance. However, the combination of traditional graphite and positive electrode is far from meeting market demand. Although the existing Si has a theoretical capacity of up to 4200mAh / g, its expansion is up to 300%, which affects the cycle performance and restricts market promotion and application.
[0003] At present, the main method to alleviate the expansion of Si negative electrode is nano-sizing, and silicon is made into nano-balls, nano-wires, etc., or porous silicon negative electrode materials are made through structural design to reserve expansion space. However, the conventional grinding method nano-sizing method has high energy consumption and difficult processing. In order to solve the problem of Si particle expansion, patent CN111009647A uses tetraethyl orthosilicate as a liquid silicon source, and obtains a multi-boron modified porous silicon composite negative electrode material through hydrothermal and metal reduction methods. However, this type of method requires the use of alkali metal reducing agents, resulting in alkali metal residues in the composite material, which will lead to reduced material stability and affect processing performance; patent CN117699772A uses porous carbon as a matrix, and deposits nano-Si on the matrix through silane deposition to obtain a silicon-carbon composite negative electrode material, but the silicon-carbon negative electrode material prepared by this type of method has a simple silicon-carbon skeleton structure with poor strength, resulting in poor stability of the electrochemical performance of the composite negative electrode material. Summary of the invention
[0004] The purpose of the present invention is to provide a silicon-boron-phosphorus alloy negative electrode material and a preparation method and application thereof, so as to solve the problems of poor processing performance and structural strength of existing silicon negative electrodes.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a silicon-boron-phosphorus alloy negative electrode material, comprising the following steps:
[0007] In a first protective gas, the biomass raw material is pre-carbonized to obtain a carbon precursor;
[0008] The carbon precursor is mixed with a base in a solid phase, and the obtained mixture is activated and acid-washed in sequence to obtain a porous carbon material;
[0009] In a second protective gas, silane gas, borane gas and phosphine gas are simultaneously used to perform a first vapor deposition on the porous carbon material to obtain a silicon-boron-phosphorus deposition porous carbon composite;
[0010] A carbon source gas is introduced into the third protective gas to perform a second vapor phase deposition on the silicon-boron-phosphorus deposited porous carbon composite to obtain a silicon-boron-phosphorus alloy negative electrode material.
[0011] Preferably, the biomass raw material includes one or more of corn stalks, fallen leaves, straw, wood chips, coconut shells, fish scales, bark, sugarcane and wheat flour; the first protective gas includes nitrogen, argon or helium; the pre-carbonization temperature is 400-800°C, and the time is 1-2h.
[0012] Preferably, the alkali includes one or more of potassium hydroxide, sodium hydroxide, calcium hydroxide, potassium carbonate and sodium carbonate, and the mass ratio of the carbon precursor to the alkali is 1:1-5.
[0013] Preferably, the activation treatment is carried out at a temperature of 500 to 1000° C. and for a time of 1 to 4 hours.
[0014] Preferably, the silane gas includes one or both of monosilane and disilane; the borane gas includes one or both of borane and diborane; the phosphine gas includes phosphine; and the second protective gas includes one or more of nitrogen, argon and helium.
[0015] Preferably, based on the total volume of the silane gas, borane gas and phosphine gas being 100%, the volume proportion of borane gas is 1-30%, the volume proportion of phosphine gas is 1-30%, and the volume proportion of silane gas is 50-90%.
[0016] Preferably, the temperature of the first vapor deposition is 500-1000° C., and the time is 1-2 hours; the flow ratio of the silane gas, borane gas and phosphine gas to the second protective gas is 50-90:1-30:1-30:50-900.
[0017] Preferably, the carbon source gas includes one or more of methane, ethane, propane, acetylene and propyne, and the third protective gas includes one or more of nitrogen, argon and helium; the flow ratio of the carbon source gas and the third protective gas is 1:1~10, the flow rate of the carbon source gas is 0.5~2L / min, the temperature of the second vapor deposition is 500~800℃, and the time is 1~3h.
[0018] The present invention provides a silicon-boron-phosphorus alloy negative electrode material prepared by the preparation method described in the above technical scheme, wherein, based on the total content of 100wt%, the Si content is 10-90wt%, the carbon content is 10-90wt%, the boron content is 0.1-50%wt, and the phosphorus content is 0.1-50wt%.
[0019] The present invention provides the application of the silicon-boron-phosphorus alloy negative electrode material described in the above technical solution in a lithium-ion battery.
[0020] The present invention provides a method for preparing a silicon-boron-phosphorus alloy negative electrode material, in which silicon is deposited and embedded in porous carbon, and phosphorus is doped in the nano silicon particles of the inner core, and the substitutional doping of phosphorus can increase the concentration of lone pair electrons in the nano silicon particles, thereby increasing the intrinsic electronic conductivity of the silicon material and reducing the internal resistance; utilizing the characteristics of the boron element, doping into the bulk phase of the silicon particles can introduce bulk defects, maintain the overall structural stability of the material, and effectively reduce the volume expansion effect of the silicon particles during the cycle. The silicon-boron-phosphorus-carbon skeleton structure in the negative electrode material prepared by the method of the present invention is stable, has the characteristics of high capacity, high rate, and ultra-long cycle, and has excellent electrochemical performance stability.
[0021] The lithium ion battery assembled from the silicon-boron-phosphorus alloy negative electrode material prepared by the present invention has excellent electrochemical performance, a capacity of 1650-2250 mAh / g, an initial efficiency of 89-93%, and a capacity retention rate of 92.1% after 50 cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The present invention is a flow chart of the method for preparing the silicon-boron-phosphorus alloy negative electrode material. DETAILED DESCRIPTION
[0023] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0024] like Figure 1 As shown, the present invention provides a method for preparing a silicon-boron-phosphorus alloy negative electrode material, comprising the following steps:
[0025] In a first protective gas, the biomass raw material is pre-carbonized to obtain a carbon precursor;
[0026] The carbon precursor is mixed with a base in a solid phase, and the obtained mixture is activated and acid-washed in sequence to obtain a porous carbon material;
[0027] In a second protective gas, silane gas, borane gas and phosphine gas are simultaneously used to perform a first vapor deposition on the porous carbon material to obtain a silicon-boron-phosphorus deposition porous carbon composite;
[0028] A carbon source gas is introduced into the third protective gas to perform a second vapor phase deposition on the silicon-boron-phosphorus deposited porous carbon composite to obtain a silicon-boron-phosphorus alloy negative electrode material.
[0029] In the present invention, the biomass raw material preferably includes one or more of corn stalks, fallen leaves, straw, wood chips, coconut shells, fish scales, bark, sugar cane and wheat flour; when the biomass raw material is two or more of the above, the present invention has no special restrictions on the ratio of different types of biomass raw materials, and any ratio is acceptable. The present invention has no special restrictions on the source and specific type of each biomass raw material, and any corresponding biomass raw material known in the art is acceptable.
[0030] In the present invention, the biomass carbon source is preferably washed, dried, crushed and sieved in sequence before being pre-carbonized. The present invention has no special limitation on the washing, drying and crushing and sieving, and can be carried out according to the processes well known in the art.
[0031] In the present invention, the first protective gas preferably includes nitrogen, argon or helium; the pre-carbonization temperature is preferably 400-800°C, more preferably 500-600°C, the time is preferably 1-2h, more preferably 2h, and the heating rate to the pre-carbonization temperature is preferably 5°C / min.
[0032] After the pre-carbonization is completed, the present invention preferably cools the obtained carbonized product to room temperature, washes it with water, dries it, and crushes it to obtain a carbon precursor; the particle size of the carbon precursor is preferably 2 to 50 μm, more preferably 20 μm.
[0033] In the present invention, the alkali preferably includes one or more of potassium hydroxide, sodium hydroxide, calcium hydroxide, potassium carbonate and sodium carbonate. When the alkali is two or more of the above alkalis, the present invention has no special limitation on the ratio of different types of alkalis, and any ratio is acceptable.
[0034] In the present invention, the mass ratio of the carbon precursor to the base is preferably 1:1-5, more preferably 1:2-3.
[0035] In the present invention, the temperature of the activation treatment is preferably 500-1000° C., more preferably 700-800° C., and the time is preferably 1-4 h, more preferably 2-3 h.
[0036] In the present invention, the acid used for pickling is preferably hydrochloric acid, and the mass fraction of the hydrochloric acid is preferably 10-50%, more preferably 37%.
[0037] After the acid washing, the present invention preferably washes the obtained product with water and then dries it to obtain a porous carbon material.
[0038] In the present invention, the silane gas preferably includes one or both of monosilane and disilane; the borane gas preferably includes one or both of monoborane and diborane; the phosphine gas preferably includes phosphine; and the second protective gas preferably includes one or more of nitrogen, argon and helium. When the silane gas, borane gas, phosphine gas or the second protective gas is two or more of the above, the present invention has no special limitation on the ratio of different types of gases, and any ratio is acceptable.
[0039] In the present invention, based on the total volume of the silane gas, borane gas and phosphine gas as 100%, the volume proportion of borane gas is preferably 1-30%, the volume proportion of phosphine gas is preferably 1-30%, and the volume proportion of silane gas is preferably 50-90%.
[0040] In the present invention, the temperature of the first vapor deposition is preferably 500-1000°C, more preferably 500-800°C, further preferably 500-600°C, and the time is preferably 1-2h; the flow ratio of the silane gas, borane gas and phosphine gas to the second protective gas is 50-90:1-30:1-30:50-900, more preferably 50-60:10:10:300.
[0041] In the present invention, the carbon source gas preferably includes one or more of methane, ethane, propane, acetylene and propyne. When the carbon source gas is two or more of the above, the present invention has no special limitation on the ratio of different types of carbon source gases, and any ratio is acceptable.
[0042] In the present invention, the third protective gas preferably includes one or more of nitrogen, argon and helium; the flow ratio of the carbon source gas and the third protective gas is preferably 1:1-10, more preferably 1:5-6; the flow rate of the carbon source gas is preferably 0.5-2L / min, more preferably 0.5-1L / min.
[0043] In the present invention, the temperature of the second vapor deposition is preferably 500-800° C., more preferably 600-700° C., and the time is preferably 1-3 hours, more preferably 2 hours.
[0044] After completing the second vapor deposition, the present invention preferably continues to introduce the third protective gas to cool down to room temperature to obtain a silicon-boron-phosphorus alloy negative electrode material.
[0045] The present invention provides a silicon-boron-phosphorus alloy negative electrode material prepared by the preparation method described in the above technical scheme, wherein, based on the total content of 100wt%, the Si content is 10-90wt%, the carbon content is 10-90wt%, the boron content is 0.1-50%wt, the phosphorus content is 0.1-50wt%, the Si content is more preferably 45-50wt%, the carbon content is more preferably 35-40wt%, the boron content is more preferably 7%wt, and the phosphorus content is more preferably 8wt%.
[0046] The present invention provides the application of the silicon-boron-phosphorus alloy negative electrode material in the above technical solution in a lithium-ion battery. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art.
[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0048] Example 1
[0049] S1. Coconut shell was used as a biomass carbon source, washed repeatedly with distilled water, placed in a 60°C drying oven for 12 h, crushed and sieved, heated to 600°C at a heating rate of 5°C / min in a nitrogen atmosphere for carbonization for 2 h, cooled to room temperature, washed with water, dried, crushed, and the crushed particle size was controlled at 20 μm to obtain a carbon precursor;
[0050] S2, mixing the carbon precursor and KOH powder in a solid phase, wherein the mass ratio of the carbon precursor to KOH is 1:2, placing the mixture in an activation furnace for activation at 800°C for 2 hours, and then washing with hydrochloric acid (mass fraction of 37%) and deionized water to remove residual alkali, and drying the mixture to obtain a porous carbon material;
[0051] S3, placing the porous carbon material in a vapor deposition furnace, raising the temperature to 500°C under a nitrogen atmosphere, introducing gases at flow rates of 0.6 / 0.1 / 0.1 / 3 L / min of silane / borane / phosphine / nitrogen, respectively, and keeping the temperature for 60 minutes, stopping the introduction of silane gas, borane gas, and phosphine, and still introducing nitrogen at 3 L / min;
[0052] S4. Heat the vapor deposition furnace to 700°C, introduce acetylene and nitrogen with flow rates of 0.5 L / min and 3 L / min respectively, keep warm for 120 min, keep nitrogen flowing at 3 L / min during cooling, and wait until it cools to room temperature to obtain a silicon-boron-phosphorus alloy negative electrode material. Based on the total content of 100wt%, the Si content is 50wt%, the carbon content is 35wt%, the boron content is 7%wt, and the phosphorus content is 8wt%.
[0053] Example 2
[0054] The only difference from Example 1 is that the coconut shell in S1 is replaced with fir bark, and the remaining steps and conditions are the same as in Example 1;
[0055] In the prepared silicon-boron-phosphorus alloy negative electrode material, based on a total content of 100wt%, the Si content is 50wt%, the carbon content is 35wt%, the boron content is 7%wt, and the phosphorus content is 8wt%.
[0056] Example 3
[0057] The only difference from Example 1 is that the flow ratio of silane gas / borane gas / phosphine / nitrogen in S3 is changed to 0.5 / 0.1 / 0.1 / 3 L / min, and the remaining steps and conditions are the same as in Example 1;
[0058] In the prepared silicon-boron-phosphorus alloy negative electrode material, based on a total content of 100wt%, the Si content is 45wt%, the carbon content is 40wt%, the boron content is 7%wt, and the phosphorus content is 8wt%.
[0059] Example 4
[0060] The only difference from Example 1 is that the temperature of the vapor deposition furnace in S4 is raised to 800° C. instead of 700° C., and the remaining steps and conditions are the same as those in Example 1;
[0061] In the prepared silicon-boron-phosphorus alloy negative electrode material, based on a total content of 100wt%, the Si content is 50wt%, the carbon content is 35wt%, the boron content is 7%wt, and the phosphorus content is 8wt%.
[0062] Example 5
[0063] The only difference from Example 1 is that the borane gas in S3 is replaced by diborane gas, and the remaining steps and conditions are the same as those in Example 1.
[0064] In the prepared silicon-boron-phosphorus alloy negative electrode material, based on a total content of 100wt%, the Si content is 50wt%, the carbon content is 35wt%, the boron content is 7%wt, and the phosphorus content is 8wt%.
[0065] Comparative Example 1
[0066] The only difference from Example 1 is that no borane gas is introduced into S3, and the remaining steps and conditions are the same as those in Example 1.
[0067] Comparative Example 2
[0068] The only difference from Example 1 is that phosphine gas is not introduced into S3, and the remaining steps and conditions are the same as those in Example 1.
[0069] Performance Testing
[0070] The performance of the negative electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 2 was tested using the following method:
[0071] Add binder, conductive agent and single-walled carbon nanotube (SCNT) to the negative electrode material, stir to make slurry, coat on copper foil, dry and roll to make negative electrode sheet; the binder used is LA132, the conductive agent is conductive carbon black (SP), and the mass ratio of negative electrode material, LA132, SP and SCNT is 94:4:1:1. The electrolyte used is LiPF6 with a concentration of 1.2 mol / L, and the solvent is a mixture of EC and DEC with a volume ratio of 1:1; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene (PP) film. The button cell is assembled in a glove box filled with argon.
[0072] Electrochemical properties The charge and discharge performance was tested on a Wuhan Blue Electric CT2001A battery tester with a charge and discharge voltage range of 0.005-2.0 V and a charge and discharge rate of 0.1 C. The rate performance (0.1-2.0 C) was also tested. The results are shown in Table 1.
[0073] Table 1 Performance data of negative electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 2
[0074]
[0075] As can be seen from Table 1, the samples in Comparative Examples 1 to 2 to which no borane or phosphine was added had significantly reduced electrochemical performance and a significantly reduced capacity retention rate. The silicon-boron-phosphorus alloy negative electrode material prepared in the present invention has a stable silicon-boron-phosphorus-carbon skeleton structure, has the characteristics of high capacity, high rate, and ultra-long cycle, and has excellent electrochemical performance stability.
[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a silicon-boron-phosphorus alloy negative electrode material, characterized in that: The following steps are involved: In a first protective gas, the biomass raw material is pre-carbonized to obtain a carbon precursor; The carbon precursor is mixed with a base in a solid phase, and the obtained mixture is activated and acid-washed in sequence to obtain a porous carbon material; In a second protective gas, silane gas, borane gas and phosphine gas are simultaneously used to perform a first vapor deposition on the porous carbon material to obtain a silicon-boron-phosphorus deposition porous carbon composite; A carbon source gas is introduced into the third protective gas to perform a second vapor phase deposition on the silicon-boron-phosphorus deposited porous carbon composite to obtain a silicon-boron-phosphorus alloy negative electrode material.
2. The preparation method according to claim 1, characterized in that: The biomass raw material includes one or more of corn stalks, fallen leaves, straw, wood chips, coconut shells, fish scales, bark, sugar cane and wheat flour; the first protective gas includes nitrogen, argon or helium; the pre-carbonization temperature is 400-800° C. and the time is 1-2 hours.
3. The preparation method according to claim 1, characterized in that: The alkali includes one or more of potassium hydroxide, sodium hydroxide, calcium hydroxide, potassium carbonate and sodium carbonate, and the mass ratio of the carbon precursor to the alkali is 1:1-5.
4. The preparation method according to claim 1 or 3, characterized in that: The activation treatment is carried out at a temperature of 500 to 1000° C. and for a time of 1 to 4 hours.
5. The preparation method according to claim 1, characterized in that: The silane gas includes one or both of monosilane and disilane; the borane gas includes one or both of borane and diborane; the phosphine gas includes phosphine; and the second protective gas includes one or more of nitrogen, argon and helium.
6. The preparation method according to claim 5, characterized in that: Taking the total volume of the silane gas, borane gas and phosphine gas as 100%, the volume of the borane gas accounts for 1-30%, the volume of the phosphine gas accounts for 1-30%, and the volume of the silane gas accounts for 50-90%.
7. The preparation method according to claim 6, characterized in that: The temperature of the first vapor deposition is 500-1000° C., and the time is 1-2 hours; the flow ratio of the silane gas, borane gas and phosphine gas to the second protective gas is 50-90:1-30:1-30:50-900.
8. The preparation method according to claim 1, characterized in that: The carbon source gas includes one or more of methane, ethane, propane, acetylene and propyne, and the third protective gas includes one or more of nitrogen, argon and helium; the flow ratio of the carbon source gas and the third protective gas is 1:1~10; the flow rate of the carbon source gas is 0.5~2L / min; the temperature of the second vapor deposition is 500~800℃, and the time is 1~3h.
9. The silicon-boron-phosphorus alloy negative electrode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: Based on the total content of 100wt%, the Si content is 10-90wt%, the carbon content is 10-90wt%, the boron content is 0.1-50%wt, and the phosphorus content is 0.1-50wt%.
10. Use of the silicon-boron-phosphorus alloy negative electrode material according to claim 9 in lithium-ion batteries.